Educar para a cidadania: promovendo auto-advocacia em grupos de pessoas com deficiência - Neves, Tânia Regina Levada (Universidade Federal de São Carlos, 2005)
This study part of the problem of special education assistance be acceded to question how we could act so that people with intellectual disability and with cerebral palsy could be been abused for the exercise of self-advocacy. From a historical review of the self-advocacy movement of persons with disabilities, of the discussion on human rights education, and new forms of participation, empowerment paradigm's standpoint, theoretical bases were substantiated which outline a methodology, based on the action research organization, involving a systematic reflection in meetings with two groups. Group 1 (G1), was composed 14 young (12 with diagnosis of cerebral palsy and two mental), aged between 25 and 38 years and history from 4 to 14 years of institutionalization. Group 2 (G2), was composed of 11 young people with intellectual disability, aged between 18 and 32 years and history of 8 to 10 years of institutionalization. In the 12 meetings weekly G1, G2 and eight with were discussed issues such as self image, perception of own working conditions, education, leisure, rights and obligations. Was noted that the participation of members of groups in the meetings was in General, intense, enthusiastic and productive in two groups, although differences should be considered. The main evidence demonstrating that if they were created significant opportunities for participation, these people would have ample opportunities to develop productive active defence of their rights. The final question is how the educational process is being conducted would not be producing dependent persons, without autonomy choices, like a child and without developing skills and knowledge that could strengthen and promote the inclusion of such persons in society. The study offers a small contribution as imagined in educating them for life.
Keywords: Estudantes com necessidades educacionais especiais; Educação para cidadania; Auto-advocacia; Autodefensoria; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL